Extended sick neonatal score in prediction of mortality of neonates transported to tertiary healthcare centre and its comparison with sick neonatal score and temperature, oxygenation, perfusion and blood sugar score - Shah, Bela H.; Gosai, Dhara; Pikle, Anurag S. (International Journal of Contemporary Pediatrics, 2020)
Background: India contributes up to 25% of neonatal mortality worldwide. Most of the times, the patient deteriorates in-transit from periphery to tertiary healthcare facility. There is a need for reliable scoring system in analysis of neonates transferred to tertiary healthcare centers in prediction of in-hospital mortality. The aim of the research was to evaluate the efficiency of extended sick neonatal score in ‘in-hospital’ mortality prediction of neonates referred to tertiary healthcare institutes and to compare it with that of other scoring systems like sick neonatal score and temperature, oxygenation, perfusion and blood sugar (TOPS) score. Methods: The research was a retrospective observational study. All extra-mural neonates admitted over a period of one month at neonatal intensive care unit (NICU) of our tertiary healthcare centre were considered after informed consent and the required parameters for scoring were assessed. Data was collected according to a pre-formed proforma. Results: Over a period of one month, 145 neonates attended on arrival were analyzed according to the mentioned systems. Various cohorts were considered. Of the systems analyzed, extended sick neonatal score had the highest sensitivity and specificity, regardless of the cohort. Conclusions: Extended sick neonatal score was more efficient than sick neonatal score and TOPS score in mortality prediction of sick neonates.